2012
DOI: 10.4238/2012.october.15.4
|View full text |Cite
|
Sign up to set email alerts
|

Two chitin metabolic enzyme genes from Hyriopsis cumingii: cloning, characterization, and potential functions

et al.

Abstract: ABSTRACT. Chitin, the second most important natural polymer in the world, and its N-deacetylated derivative chitosan are found in a wide variety of organisms. These versatile biopolymers are associated with a broad range of biological functions. This article is the first to report the potential functions of 2 chitin metabolic enzyme genes from Hyriopsis cumingii. A chitinase-3 gene (Chi-3) and a chitin deacetylase gene (Cda) were cloned from H. cumingii and characterized. Semi-quantitative reverse transcriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The full-length cDNA of A. kurodai ovotestis chitinase (AkChi) was 1352 bp in length and contained an ORF of 1263 bp encoding 421 amino acids (Figure 2). The size of ORF of AkChi was smaller than it from H. cumingii [14], 1962 bp encoding 653 amino acids. A poly-A sequence in eukaryotes was detected at the 3' end of AkChi.…”
Section: Cloning Of a Kurodai Chitinase Cdnamentioning
confidence: 87%
See 2 more Smart Citations
“…The full-length cDNA of A. kurodai ovotestis chitinase (AkChi) was 1352 bp in length and contained an ORF of 1263 bp encoding 421 amino acids (Figure 2). The size of ORF of AkChi was smaller than it from H. cumingii [14], 1962 bp encoding 653 amino acids. A poly-A sequence in eukaryotes was detected at the 3' end of AkChi.…”
Section: Cloning Of a Kurodai Chitinase Cdnamentioning
confidence: 87%
“…The catalytic domain also contained an active site that is a conserved sequence of GH family 18 chitinases (Figure 3). Though the chitinase of H. cumingii [14] and E. scolopes [15] had two chitin binding domains (CBDs) and the chitinase of S. esculenta had one CBD, AkChi lacked a CBD. It was reported that fish chitinases have one CBD [8].…”
Section: Cloning Of a Kurodai Chitinase Cdnamentioning
confidence: 99%
See 1 more Smart Citation
“…Growth of the crystal is strictly regulated throughout mussel development, and various experimental systems have indicated that the proteins associated with shell formation differ on the basis of the genetic background of each particular species. A wide variety of bio-minerals play a key role in regulating the growth, shape and physical properties of materials, such as shells and pearls (Butler, 1998;Wilt, 1999;Fincham et al, 1999;Myllyharju and Kivirikko, 2001;Wang, et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Chitinases in the fish stomach are classified into two groups based on differences in their primary structure and the patterns of degradation of (GlcNAc) n : acidic fish chitinase-1 (AFCase-1) and acidic fish chitinase-2 (AFCase-2) [16] [17] [18] [19]. Conversely, studies reporting the cDNA cloning and expression of chitinases and chitinase-like proteins from bivalves and gastropods, which are mollusks, have noted that these play roles in shell formation [20] [21] [22], immunity [23] [24] [25] [26], and digestion [27]. Chitinase isozymes have been purified and studied from the liver of Decembrachiata (squid and cuttlefish), and are involved in digestion [28] [29] [30] [31].…”
Section: Introductionmentioning
confidence: 99%